2014
DOI: 10.1111/bpa.12148
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Infiltrative Behavior of Adamantinomatous Craniopharyngioma in a New Xenotransplant Mouse Model

Abstract: Adamantinomatous craniopharyngiomas (adaCP) cause hypothalamic pituitary dysfunction. Elucidation of pathomechanisms underlying tumor progression is essential for the development of targeted chemotherapeutic treatment options. In order to study the mechanisms of tumor outgrowth, we implanted human primary adaCP tissue from three different surgical specimens stereotactically into the brain of immunodeficient mice (n = 20). Three months after tumor inoculation, magnetic resonance imaging and histology confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…MRI of nude mice bearing cerebral patient‐derived ACP xenografts was performed between 124 and 130 days after tumor implantation, at which time successful tumor engraftment had previously been confirmed histologically 26, under isoflurane anesthesia, on a 7T horizontal bore microimaging system (Bruker, Ettlingen, Germany) equipped with a dedicated mouse brain coil and an animal monitoring system. T 2 ‐weighted images ( T R  = 2370 ms, T E  = 41 ms, slice thickness = 0.7 mm, FOV = 24 mm × 38 mm, 210 × 320 matrix, pixel size = 119 µm × 119 µm) and T 1 ‐weighted contrast‐enhanced images prior to and following intravenous administration of 0.1 mmol/kg gadobutrol (Gadovist, Bayer Vital, Leverkusen, Germany) ( T R  = 500 ms, T E  = 9 ms, slice thickness = 0.7 mm, FOV = 24 mm × 28 mm, 448 × 512 matrix, pixel size = 55 µm × 55 µm) were acquired.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI of nude mice bearing cerebral patient‐derived ACP xenografts was performed between 124 and 130 days after tumor implantation, at which time successful tumor engraftment had previously been confirmed histologically 26, under isoflurane anesthesia, on a 7T horizontal bore microimaging system (Bruker, Ettlingen, Germany) equipped with a dedicated mouse brain coil and an animal monitoring system. T 2 ‐weighted images ( T R  = 2370 ms, T E  = 41 ms, slice thickness = 0.7 mm, FOV = 24 mm × 38 mm, 210 × 320 matrix, pixel size = 119 µm × 119 µm) and T 1 ‐weighted contrast‐enhanced images prior to and following intravenous administration of 0.1 mmol/kg gadobutrol (Gadovist, Bayer Vital, Leverkusen, Germany) ( T R  = 500 ms, T E  = 9 ms, slice thickness = 0.7 mm, FOV = 24 mm × 28 mm, 448 × 512 matrix, pixel size = 55 µm × 55 µm) were acquired.…”
Section: Methodsmentioning
confidence: 99%
“…Lesions propagated in this manner show comparable tissue architecture and express similar immunohistochemical markers to the patient tumors, including whorl‐like cell clusters with nuclear β‐catenin accumulation and activated EGFR 26.…”
Section: Introductionmentioning
confidence: 92%
“…To model the disease, fresh surgically obtained ACP tissue has been used in vitro to isolate primary cell cultures, and recently, a new orthotopic xenograft model has been described. 12,22,50 Two genetically engineered models, expressing a functionally equivalent form of oncogenic b-catenin to that identified in human ACP, have given valuable insights into the processes underling tumorigenesis. 3,4,15 It is likely that to translate any new findings into novel therapeutic opportunities, a multidisciplinary approach combining several or all of these existing methodologies and perhaps new assays (e.g., circulating cell-free DNA (cfDNA) and proteomics) will be required.…”
Section: Methodologies Used To Understand the Molecular Pathology Of Acpmentioning
confidence: 99%
“…Logically, the activities of the clusters must be required to support tumour viability; otherwise, one must call into question why the scarce non-dividing cells are not eliminated, even though normal pituitary cells are mostly killed by the dividing tumour cells. In fact, using a xenograft mouse model, the Buslei group has shown that clusters are critical players in controlling cell behaviour and the infiltration of other tumour cells (Stache et al 2014). The paracrine model for the involvement of tissuespecific adult stem cells in tumorigenesis suggests that the cell that sustains the oncogenic mutation (mutant CTNNB1) and the cell-of-origin of the tumours are different (Fig.…”
Section: Intriguingly When Sox2mentioning
confidence: 99%
“…In addition, these and a recent xenograft model (Stache et al 2014) represent a platform for testing novel treatments in pre-clinical studies.…”
Section: Childhood-onset Acps Are Likely To Be Developmental Tumoursmentioning
confidence: 99%